Study to assess knowledge, attitude and practice regarding swine flu vaccine amongst medical students - Solunke, Rajvardhan R.; Dharmadhikari, Shrikant C.; Jaju, Jugalkishore B.; Pawar, Ganesh R.; Gurung, Aruna (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Due to recurrent outbreak and associated high mortality of swine flu there is panic amongst medical students also because of higher risk of getting infected. Vaccination for swine flu is the best preventive measure. So this study was undertaken. The aim of the present study was to assess the knowledge, attitude and practice regarding swine flu vaccine amongst medical students of government medical college and provide data to improve awareness about swine flu vaccine Methods: This was a cross sectional observational study carried out amongst 250 medical students during period of April-June 2015. A pre designed and pre tested, multiple choice questionnaires was used to assess KAP regarding swine flu vaccine and descriptive analysis was done. Results: Knowledge of participants regarding Swine flu vaccine was high as the mean score of correct answers marked was 152.5. But Only 21.8% participants had knowledge about cost of vaccine and 33.2% about the adverse drug reactions to the vaccine. Internet was the most common source of information amongst participants. Attitude of participants toward vaccination was favourable (mean score -128.4) but attitude for vaccination during pregnancy (30.8%) and with other vaccines (32.8%) was unfavourable. Only 30(12%) candidates have taken the vaccine which shows very poor practice. Conclusions: This study shows high knowledge, favourable attitude but poor practice towards Swine flu vaccination amongst medical students. So there is need to increase awareness for vaccination of swine flu amongst medical students by continuous health education and also need to increase the availability of vaccine in government hospitals.